2011
DOI: 10.5301/ru.2011.8886
|View full text |Cite
|
Sign up to set email alerts
|

Overactive Bladder Syndrome: The Social and Economic Perspective

Abstract: Overactive bladder syndrome (OAB) is a highly prevalent condition associated with a significant impairment of patients' Quality of Life (QoL) because of its adverse effects on social, sexual, interpersonal, and professional functions. Cost-of-illness analyses showed the huge economic burden related to OAB for patients, public healthcare systems, and society, secondary to both direct and indirect costs. These types of cost analyses, however, exclude intangible costs related to QoL impairment. Recently, many nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 142 publications
(214 reference statements)
0
3
0
Order By: Relevance
“…Several previous studies reported associations of medical comorbidities with OAB, including metabolic syndrome and stroke [8, 12]. Diabetes was especially related to bladder dysfunction, which occurs in 80% of diabetic patients [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous studies reported associations of medical comorbidities with OAB, including metabolic syndrome and stroke [8, 12]. Diabetes was especially related to bladder dysfunction, which occurs in 80% of diabetic patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…OAB is known to be detrimental to the overall quality of life because of its impact on physical, emotional, and social aspects [3, 7, 8]. OAB is related to the various psychological problems of sleep disturbance, low self-esteem, depression, and anxiety as well as urinary complaints and subsequent diminished sexual activity [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation